M28 From NEWS to CREWS: The chronic respiratory early warning score for patients with chronic hypoxaemia. (14th November 2013) - Eccles, SR; Subbe, C; Hancock, D; Thompson, N
Abstract : Introduction: In patients with respiratory conditions associated with chronic hypoxaemia such as COPD, use of the National Early Warning Score (NEWS)[1] leads to a high number of triggers. We designed a simple variant of NEWS for patients with chronic hypoxaemia. Methods: Data was collected from respiratory wards at two hospitals in North Wales over a three-month period. Patients were categorised into those with chronic hypoxaemia (CH, target oxygen saturations 88–92%) and others (O, target saturations 94–98%). Vital signs were recorded on admission to hospital, at the peak NEWS score during admission, and during a period of stability/at discharge. Results: 196 admissions were included in the analysis. 98 (50%) were male, 91 had COPD, 26 received long-term oxygen therapy. Mean age was 70 (range 19–102). 78 patients had target saturations of 88–92% (CH patients). The mean NEWS for all patients on admission was 5 (SD 3), mean peak NEWS was 7 (SD 3), and median hospital length of stay was 10 days (IQR 6:17). 23 patients died within 30 days; 12 with CH. Of these, all patients with CH scored 6 + using NEWS compared to 9/11 O patients. When stable/at discharge, 32% of CH patients scored 6 + using NEWS (Welsh trigger) and 50% scored 5 + (RCP trigger). By using a recalibrated scoring system (CREWS, table 1 ), patients triggering during stability/at discharge were reduced to 14% (5 + trigger) and 8% (6 + trigger). All patients who subsequently died still triggered at peak CREWS scores. Conclusion: Patients with chronic respiratory conditions have altered baseline parameters that lead to a high number of NEWS triggers. CREWS reduces triggers, which may reduce unnecessary reviews and alarm fatigue, without compromising safety. Reference: Royal College of Physicians. National Early Warning Score (NEWS): Standardising the assessment of acute illness severity in the NHS. Report of a working party. London: RCP, 2012.